Analysis of Student Learning Difficulties in Integrated Social Studies Subjects in Class VIII - Zendrato, Ratih Ceriani; Harefa, Yearning; Telaumbanua, Wahyutra Adilman; Laoli, Bezisokhi (Golden Ratio of Data in Summary, 2024)
The main problem in this study is the low understanding of class VIII UPTD SMP Neger 1 Gunungsitoli students related to Integrated Social Studies subjects. Learning difficulties have an impact on the activities of students in the classroom who tend to be passive and do not play an active role. The purpose of this study was to determine learning difficulties in social studies learning in students at UPTD SMPN 1 Gunungsitoli Utara. In this study researchers used qualitative research methods. The results of the research conducted, it is known that the factors that influence students' learning difficulties include internal and external factors. Internal factors include the minimal interest in learning of students and the low level of learning ability of students so that it affects low learning outcomes, as well as external factors which include lack of attention from parents and the way teachers teach that has not hit students. It can be concluded that students have difficulty learning social studies, caused by external and internal factors.